Formation of Andrographlolide-BetaCyclodextrin Inclusion to Increase Solubility and Dissolution Rate - Prasetyo, Bayu Febram; Wientarsih, Ietje; Sajuthi, Dondhin; Juniantito, Vetnizah (Indonesian Journal of Pharmaceutical Science and Technology, 2018)
Andrographolide (AG) is a pure isolate of the chemical synthesis of sambiloto (Andrographis paniculata Nees.) which has various pharmacological properties such as anti-inflammatory and antimicrobial. In order to improve the ability of AG to penetrate the membrane in transdermal use, an inclusion complex was formed using beta-cyclodextrin (BCD) by modifying the physical chemistry properties of AG, particularly the solubility in its base, partition, and distribution on the skin, as well as by changing the permeability of the stratum corneum. The inclusion complexes of AG with BCD were prepared by the solvent evaporation method in the mole ratios of 1:1, 1:2, and 2:1. The solid of the yield of AG inclusion complex in BCD has been tested with a solubility test until it reached equilibrium at 37 ± 5 °C for 24 hours and In vitro dissolution rate test using the II USP method (paddle type), then compared to a single AG compound, and a physical mixture of AG-BCD. Based on the solubility and dissolution rate tests, it showed that the formation of AG-BCD inclusion complex was obtained at the mole ratio of 1:2. Moreover, the AG solubility increased 38 timesand the dissolution rate in the 60th minute increased twice  in the inclusion complex with BCD.Key words: andrographolide, inclusion complex, beta cyclodextrin, solubility, dissolution rate